EXPLORING EDUCATIONAL PATHS: UNVEILING CONTRASTS BETWEEN INDONESIA’S CURRICULUM AND HONG KONG’S CURRICULUM - Yawan, Hendri; Furqan, Al; Karman, Karman; Sarmadan, Sarmadan; Reskiawan, Bimas (Sanata Dharma University Yogyakarta, 2023)
This study aims to conduct a comparative analysis of the development of Indonesia's curriculum and Hong Kong's curriculum, with a focus on identifying the underlying philosophical values and influences embedded in both educational systems. The research also explores the implications of these curricula on various stakeholders involved in their development and implementation. To achieve these objectives, a synthesis research approach was employed, analyzing a combination of empirical and conceptual papers to draw robust conclusions. The study yielded four key findings that shed light on public opinions, philosophy, goals, and implications of the curricula. Firstly, both the Indonesian curriculum and the Hong Kong curriculum received predominantly positive responses from stakeholders, with minor complaints reported through official surveys. Secondly, the philosophical foundation of the Indonesian curriculum centers around social justice, while the Hong Kong curriculum places a strong emphasis on diversity and inclusivity. Furthermore, both curricula have implicit purposes that can be inferred from the range of topics covered in the respective curriculum guidebooks. Finally, the implementation of these curricula has led stakeholders in each country to issue policies aimed at consolidating their influence. In Hongkong, the promotion of the Chinese-based course serves to strengthen China's power in the field of English education. Conversely, in Indonesia, efforts have been made to preserve the Indonesian language by removing the English subject at the primary level and reducing the time allocation for English in secondary education. This study contributes to a deeper understanding of the development and influences of curricula in Indonesia and Hong Kong, providing valuable insights for policymakers, educators, and researchers.